Winter's bone [videorecording (DVD)] - Granik, Debra; Lawrence, Jennifer, 1990-; Hawkes, John, 1959-; Breznahan, Kevin, 1968-; Dickey, Dale; Woodrell, Daniel (Lionsgate, 2010)
Seventeen-year-old Ree Dolly sets out to track down her father who put their house up for his bail bond and then disappeared. If she fails to find him, she and her family will be turned out into the Ozark woods. Challenging her outlaw kin's code of silence and risking her life, Ree hacks through the lies, evasions, and threats offered up by her relatives and begins to piece together the truth.